Off-Road Motorbike Performance Analysis Using a Rear Semiactive EH Suspension - Jorge de-J. Lozoya-Santos; Damián Cervantes-Muñoz; Juan Carlos Tudón-Martínez; Ricardo A. Ramírez-Mendoza (Shock and Vibration)
The topic of this paper is the analysis of a control system for a semiactive rear suspension in an off-road two-wheeled vehicle. Several control methods are studied, as well as the recently proposed Frequency Estimation Based (FEB) algorithm. The motorcycle dynamics, as well as the passive, and semiactive dampers, and the algorithm controlled shock absorber models are loaded into BikeSim, a professional two-wheeled vehicle simulation software, and tested in several road conditions. The results show a detailed comparison of the theoretical performance of the different control approaches in a novel environment for semiactive dampers.